Incidence of lower limb amputation in people with and without diabetes: a nationwide 5-year cohort study in Japan - Sadanori Okada; Yasuhiro Akai; Tatsuya Noda; Tomoaki Imamura; Yutaka Takahashi; Fumika Kamitani; Yuichi Nishioka; Tomoya Myojin; Shinichiro Kubo; Tsuneyuki Higashino; Hitoshi Ishii (BMJ Open)
Introduction This study was conducted to investigate the incidence and time trend of lower limb amputation (LLA) among people with and without diabetes.Research design and methods This retrospective population-based cohort study was based on the national claims data in Japan, comprising a total population of 150 million. Data of all individuals who had LLA from April 2013 to March 2018 were obtained. We analysed the sex-adjusted and age-adjusted annual LLA rate (every fiscal year) in people with and without diabetes for major and minor amputation. To test for time trend, Poisson regression models were fitted.Results In the 5-year period, 30 187 major and 29 299 minor LLAs were performed in Japan. The sex-adjusted and age-adjusted incidence of major and minor LLAs was 9.5 (people with diabetes, 21.8 vs people without diabetes, 2.3, per 100 000 person-years) and 14.9 (people with diabetes, 28.4 vs people without diabetes, 1.9, per 100 000 person-years) times higher, respectively, in people with diabetes compared with those without. A significant decline in the annual major amputation rate was observed (p<0.05) and the annual minor amputation rate remained stable (p=0.63) when sex, age and people with and without diabetes were included as dependent variables.Conclusions This is the first report of the national statistics of LLAs in Japan. The incidence of major and minor LLAs was 10 and 15 times higher, respectively, in people with diabetes compared with those without. A significant decline in the major amputation rate was observed, and the annual minor amputation rate remained stable during the observation period. This information can help to create an effective national healthcare strategy for preventing limb amputations, which affect the quality of life of patients with diabetes and add to the national healthcare expenditure.